Pelatihan Budidaya Ikan Lele Sistem Bioflok untuk Karang Taruna Tirta Bahari Sorong - sukmawati, sukmawati; Ponisri, Ponisri; Fajeriana, Nurul; Mangallo, Bertha; Musaad, Ishak; Lestari, Agnes Dyah Novitasari (Penerbit Goodwood, 2025)
Purpose: The catfish farming training using the biofloc system conducted for the Tirta Bahari Youth Group in Jamaimo Village aims to enhance the skills and knowledge of the fisheries group in utilizing biofloc technology as an efficient, sustainable, and environmentally friendly aquaculture method. Methodology: The biofloc system boosts fish farming productivity by using microorganisms to process feed waste and excrement into an additional nutrient source. Results: This training covered biofloc pond design, introduction of microorganisms, water quality monitoring for catfish growth, and maintenance management through aeration control and measurement of key parameters, such as pH, dissolved oxygen, and ammonia, to maintain pond stability. Conclusions: This training is expected to enhance the knowledge and skills of the Tirta Bahari Youth Group in biofloc-based fish farming, enabling them to apply it independently and sustainably. In the long term, this initiative is expected to strengthen the local economy by creating business opportunities in the aquaculture sector, enhancing food security, and empowering the Tirta Bahari Youth Group and other youth as agents of change who can contribute to sustainable fishery resource use in Jamaimo Village. Limitations: The time available for training may not be sufficient to cover all technical aspects in depth; therefore, participants may not be fully prepared to implement the biofloc system independently. Contribution: This service can have a wide and sustainable positive impact on the Jamaimo Village community.